Arctic National Wildlife Refuge (ANWR): Controversies for the 109th Congress - Corn, M. Lynne; Gelb, Bernald A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2006)
This report provides information about Arctic National Wildlife Refuge (ANWR) and controversies for the 109th congress.